Development of digital technology-based nursing service innovation in the pandemic era - Yulis Setiya Dewi; Nursalam Nursalam; Ahsan Ahsan; I Ketut Eddy Purnama; Tomoko Hasegawa; Arina Qona'ah; Rifky Octavia Pradipta; Hidayat Arifin; Gusmaniarti Gusmaniarti (Universitas Muhammadiyah Magelang, 2022)
Optimizing health services during the pandemic is something that hospitals must do in order to keep improving service quality. This community service aims to educate nurses on how to use digital technology-based nursing services in the pandemic. Health education is provided through webinars, as a method of implementing this community service program. The majority of webinar participants (60%) had sufficient knowledge based on the results of the pretest. Following the presentation of the material, it can be concluded that there has been an increase in knowledge, with 182 participants (90%) having excellent knowledge. Nursing services are benefiting from digital innovation not only in terms of workforce management, but also in terms of changing the way care is delivered. Nurses are crucial in the adoption of digital tools and information technology to improve patient care. This is due to the fact that the quality of digital care delivery has risen to the forefront of healthcare and is being scrutinized more than ever before.